Use of the Apple Watch iECG in adult congenital heart disease patients - Stephan Striepe; Anna Michaelis; Franziska Markel; Philipp Kalden; Florian Löffelbein; Andreas Bollmann; Alireza Sepehri Shamloo; Ingo Dähnert; Roman Antonin Gebauer; Christian Paech (Indian Pacing and Electrophysiology Journal, 2022)
Introduction: This study evaluates the accuracy of iECGs in comparison to the gold standard ECG in adult patients with congenital heart disease and recommends the appropriate iECG derivation based on the patient's characteristics. Methods: In 106 adults (51 female, 55 male) with congenital heart disease, a gold standard 12-lead ECG was recorded, followed by three iECGs with the Apple Watch series 4, which correspond to Einthoven leads I, II, and III. Two experienced and independent cardiologists analyzed the time intervals, amplitudes, and polarities of the ECG parameters as well as the rhythm type and correlated the patient characteristics with the iECG parameters. Results: The iECG parameters of all three iECG leads correlate strongly with those of the gold standard ECG, with exception of the P and T wave durations. We demonstrated that the informative value of the individual iECGs was independent of the patient's characteristics, in particular the heart axis, anatomy, and situs, even if the quality of the Einthoven III-like derivation was partially inadequate. The automatic rhythm analysis of the Apple Watch and the heart rhythm classification of a standard ECG analyzed manually by a cardiologist corresponded in 77%. Conclusion: iECG recordings of adults with congenital heart disease provide comparable results with Einthoven recordings I, II, and III of the 12-lead ECG and current data encourage the use of the Apple Watch not only in patients with structurally normal hearts but also in patients with congenital heart disease.